2022
DOI: 10.3389/fnut.2022.915558
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics approach reveals high energy diet improves the quality and enhances the flavor of black Tibetan sheep meat by altering the composition of rumen microbiota

Abstract: This study aims to determine the impact of dietary energy levels on rumen microbial composition and its relationship to the quality of Black Tibetan sheep meat by applying metabolomics and Pearson's correlation analyses. For this purpose, UHPLC-QTOF-MS was used to identify the metabolome, whereas 16S rDNA sequencing was used to detect the rumen microbiota. Eventually, we observed that the high energy diet group (HS) improved the carcass quality of Black Tibetan sheep and fat deposition in the longissimus lumbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 60 publications
0
20
1
Order By: Relevance
“…For amino acid (AA) analysis, an Agilent 1290 Infinity LC ultra‐high‐performance liquid chromatography system (Agilent, Waldbronn, Germany) was used along with a 5500 QTRAP mass spectrometer (AB SCIEX). The conditions used for the high‐performance liquid chromatography and mass spectrometry were as described by Zhang, Han, Hou, Raza, Gui, et al ( 2022 ). The HPLC conditions were as follows: the mobile phase: 25 mM ammonium format +0.08% FA aqueous solution for liquid A and 0.1% FA acetonitrile for liquid B.…”
Section: Methodsmentioning
confidence: 99%
“…For amino acid (AA) analysis, an Agilent 1290 Infinity LC ultra‐high‐performance liquid chromatography system (Agilent, Waldbronn, Germany) was used along with a 5500 QTRAP mass spectrometer (AB SCIEX). The conditions used for the high‐performance liquid chromatography and mass spectrometry were as described by Zhang, Han, Hou, Raza, Gui, et al ( 2022 ). The HPLC conditions were as follows: the mobile phase: 25 mM ammonium format +0.08% FA aqueous solution for liquid A and 0.1% FA acetonitrile for liquid B.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the experiment, 15 lambs with five lambs per treatment were provided with free access to drinking water and fasted The blood samples were immediately carried out from the jejunum and transferred to the laboratory for analysis of serum biochemistry. Synchronously, the rumen fluid was collected by four layers of gauze for the ruminal fermentation and microorganism analyses (Zhang et al, 2022).…”
Section: Sample Collectionmentioning
confidence: 99%
“…BTS meat is quite popular for its unique flavor, texture, and nutritional value. Previously, we reported that BTS meat has high nutritional value with high protein and amino acids content and low-fat content [2]. Concerning the sensory value, BTS meat is more tender, less fibrous, and chewy.…”
Section: Introductionmentioning
confidence: 95%
“…of one breed BTS is better than others such as the White Tibetan sheep. The current research mainly focuses on the effect of feed on the meat quality, rumen parameters, and growth performance of BTS [2,3], while the effect of different heat processing methods on the meat characteristics of BTS is largely unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation